Expression of cytokines on the iris of patients with neovascular glaucoma. (13th July 2014) - Hou, Xian‐ru; Miao, Heng; Tao, Yong; Li, Xiao‐xin; Wong, Ian Y.
Abstract Purpose To determine the expression levels of cytokines, including growth factors, inflammatory cytokines, and cell migration associated factors on the iris from subjects with neovascular glaucoma (NVG). Methods After receiving formal consent from 12 subjects with NVG secondary to proliferative diabetic retinopathy and 12 subjects with primary open angle glaucoma (POAG), trabeculectomy was performed and iris specimens were collected during the surgery. Each subject with NVG received intravitreal injection of bevacizumab 1 week prior to the surgery. The mRNA level of vascular endothelial growth factor, basic fibroblastic growth factor, placental‐induced growth factor, interleukin‐2, interleukin 6, tumour necrosis factor α, intercellular adhesion molecule 1 (ICAM‐1) and integrin subunit αV were determined by real‐time polymerase chain reaction. The mRNA levels were compared between the two groups. Results The mRNA levels of all inflammatory cytokines and integrin subunit αV were significantly increased in the NVG group compared with POAG controls. However, the mRNA level of growth factors and ICAM‐1 did not show any difference between the two groups. Conclusions Inflammatory process maybe an important cause of iris neovascularization in subjects with NVG in addition to growth factors alone. Further studies should focus on the effect of growth factors in different phases in the pathogenesis of NVG.